Clinical outcomes of a digitally supported approach for self-management of type 2 diabetes mellitus - De Luca, Vincenzo; Bozzetto, Lutgarda; Giglio, Clemente; Tramontano, Giovanni; De Simone, Giuseppina; Luciano, Antonio; Lucibelli, Luigi; Maffettone, Ada; Riccio, Michele; Romano, Geremia; Rossi, Ernesto; Chiatti, Carlos Juan; et al. (Frontiers in Public Health, 2023)
Background Self-management of Type 2 diabetes mellitus (T2D) is challenging. Regular self-monitoring of blood glucose and healthy lifestyles are required to improve glycometabolic control, thus delaying diabetes complications, and reducing hospitalizations. Digital technologies can empower patients in their disease management promoting self-management and motivation to change behaviors. We report the results of an exploratory trial aimed at evaluating the metabolic outcomes of using digital solutions for T2D self-management developed in the ProEmpower project, a European Commission funded Pre-Commercial Procurement. Methods Two digital solutions, DM4All and DiaWatch, which were codesigned with providers, patients, and caregivers, enabled the collection of clinical parameters by the patient using a smartphone integrated with the medical devices (glucometer, sphygmomanometer, scale, smart watch for heart rate monitoring and step counter). Data were automatically sent to the shared care plan allowing professionals to monitor adherence to treatment, set goals, and communicate more effectively with patients. At baseline and after an average follow-up of 8 months, glycosylated hemoglobin (HbA1c), body weight, blood pressure, and blood lipids were measured in 100 T2D patients using the ProEmpower solutions across different diabetes centers in Campania Region, age 45–79 years, both genders, and compared with a Control cohort of T2D patients (n = 100) with similar clinical characteristics and followed for a comparable period of observation in the same centers. Results At baseline, the ProEmpower participants and the Control subjects were on average overweight, with a similar BMI in the two cohorts, and mean HbA1c was at acceptable levels (around 7.0%). After the 8 month exploratory trial, body weight, HbA1c, systolic and diastolic blood pressure, and plasma and LDL-cholesterol significantly decreased in the ProEmpower participants compared to baseline (p < 0.05 for all). The changes in systolic and diastolic blood pressure, and plasma and LDL-cholesterol were significantly different from those observed in the Control cohort (p < 0.05 for all). Conclusion This pilot study showed positive effects on metabolic outcomes relevant to cardiovascular risk in T2D of adopting digital telemedicine self-monitoring solutions based on automation of measurements and coaching on healthy lifestyles promotion.